Mastitis Tuberkulosis Primer - Irene R T Damanik (PT FORMOSA CENDEKIA GLOBAL, 2023)
Objectives : Tuberculous (TB) mastitis is an uncommon presentation of TB even in countries where the incidence of pulmonary and extrapulmonary TB is high. It accounts for < 0.1% of all breast pathologies and <2% of all cases of tuberkulosis. Case presentation : A 25-year-old female presented a palpable lump in the upper-outer quadrant left breast, measuring about 3 cm and accompanied by retraction of the adjacent skin. Conclusion : Tuberculous mastitis is a rare and results from direct infection via the breast ducts opening to the nipple or from breast skin abrasions. Breast sonography and fine needle aspiration biopsy have been used for diagnostic of tuberculous mastitis.